Teh Celup Daun Pepaya (Carica papaya) Solusi Alami Antihipertensi di Dusun Tanah Abang, Desa Mersam - Trifah, Rahmadha; Marisanti, Debi Putri; Siti Nurul Khoiriyah; Bella Melyani; Prima, Nurmalinda; Hutagalung, Bertha Uli; Ningsih, Ayi Setiya; Verra Veriska, Pretty Sepvanny; Devianti, Dina Nazifa; David Usmany, Abdillah (Jurnal Abdimas Kesehatan (JAK), 2025)
A community service activity with the theme "Papaya Leaf Tea Bags as Antihypertensive" has been carried out in Tanah Abang Hamlet, Mersam Village, Jambi Province, on January 12, 2025. This program aims to increase public knowledge about hypertension and the use of papaya leaves as an alternative to traditional medicine. The methods used include counseling, demonstrations, discussions, and questions and answers. The material presented included the definition of hypertension, causes, prevention, and how to process papaya leaves into tea bags. The results of the activity show the high enthusiasm of the community in understanding and practicing the making of papaya leaf tea bags. This program has succeeded in increasing public awareness of the importance of controlling hypertension through the use of natural ingredients, which is indicated by a significant increase in public knowledge of 80% after the activity was implemented. It is hoped that this activity can have a positive impact on hypertension control and public health in Mersam Village in a sustainable manner.